High-precision dating of volcanic events (A.D. 1301-1995) using ice cores from Law Dome, Antarctica - AS Palmer; Tasman van Ommen; MAJ Curran; VI Morgan; JM Souney; PA Mayewski (2001)
A record of volcanic activity over the period A.D. 1301-1995 has been extracted from three Law Dome ice cores (East Antarctica). The record dating is unambiguous at the annual level from A.D. 1807 to 1995 and has an uncertainty of Â±1 year at A.D. 1301. Signals from 20 eruptions are preserved in the record, including those of two unknown eruptions with acid deposition beginning in A.D. 1810.8 and A.D. 1685.8. The beginning of the ice core signal from the A.D. 1815 Tambora eruption is observed in the austral summer of A.D. 1816/1817. The mean observed stratospheric transport and deposition time to Law Dome from the eruption site is 1.5 years (Ïƒ = 0.6 years) from 11 well-dated eruptions. The largest eruption observed in the Law Dome record has its maximum in A.D. 1460 with volcanic sulfate deposition beginning in the austral winter of A.D. 1459. This event is also observed in other ice core records and is attributed to the volcano Kuwae, with an eruption date in the range A.D. 1455.9-1459.9 if all sources of error are considered. This is at least three years later than the date previously ascribed by dendrochronological and historical studies. Copyright 2001 by the American Geophysical Union.